2021
DOI: 10.3390/rel12040284
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of Self-Dignity and Anger among Polish Young Adults: The Moderating Role of Religiosity

Abstract: Does the way we think or feel about ourselves have an impact on our anger-based reactions? Is the direction and strength of this relationship direct, or affected by other factors as well? Given that there is a lack of research on the loss of self-dignity and anger, the first aim of the present study consisted in examining whether or not there is a connection between both variables, with particular emphasis on early adulthood. The second purpose was to explore the moderating role of religiosity on the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Brudek and Steuden (2017b) showed that religious meaning system is positively related to sense of self-dignity. In another study Rodzeń et al (2021) showed low and negative relationship between the loss of self-dignity, and the religious meaning system among young adults. Thus, religious meaning system seems to be a protective factor in the sense of self-dignity.…”
Section: Gerotranscendence and Religious Meaning System Wisdom Sense ...mentioning
confidence: 91%
“…Brudek and Steuden (2017b) showed that religious meaning system is positively related to sense of self-dignity. In another study Rodzeń et al (2021) showed low and negative relationship between the loss of self-dignity, and the religious meaning system among young adults. Thus, religious meaning system seems to be a protective factor in the sense of self-dignity.…”
Section: Gerotranscendence and Religious Meaning System Wisdom Sense ...mentioning
confidence: 91%
“…However, as Muslim, the guidelines contained in the Quran and Hadith should be first followed (that is by putting religion as basic education in personality development of adolescents). Spiritual approach is important as adolescents who appreciate the morals and principles of religion are less likely to engage in delinquent activities [23], [24] and are better in managing their anger [25]. Many therapists have used psycho-spiritual interventions to address their client's psychological well-being and personal development needs.…”
Section: Introductionmentioning
confidence: 99%